2000
DOI: 10.1002/(sici)1521-3927(20000301)21:6<243::aid-marc243>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of tethered chains in various solution conditions using Langmuir diblock copolymer monolayers

Abstract: This article summarizes our investigations of tethered chain systems using Langmuir monolayer of polydimethysiloxane-poly styrene (PDMS-PS) diblock copolymers on organic liquids. In this system, the PDMS block adsorbs to the air surface while the PS block dangles into the subphase liquid. The air surface can be made either repulsive or attractive for the tethered PS chain segments by choosing a subphase liquid which has a surface tension lower or greater than that of PS, respectively. The segment profile of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 81 publications
(172 reference statements)
6
111
1
Order By: Relevance
“…[29][30][31] The surface and solvent were chosen to maximize preferential adsorption of one block to a solid surface while the solvent was chosen to preferentially interact with the other block. One example is the physisorption of polystyrene-b-poly(ethylene oxide) (PS-b-PEO) from a toluene solution.…”
Section: Synthesis Of Grafted Polymer Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] The surface and solvent were chosen to maximize preferential adsorption of one block to a solid surface while the solvent was chosen to preferentially interact with the other block. One example is the physisorption of polystyrene-b-poly(ethylene oxide) (PS-b-PEO) from a toluene solution.…”
Section: Synthesis Of Grafted Polymer Chainsmentioning
confidence: 99%
“…However, this value is strongly affected by excluded volume and can vary from system to system. For example, Kent 29 studied Langmuir-Blodgett layers of poly(dimethylsiloxane)-b-PS block copolymers and reported that the highly stretched regime occurs for S [ 12. A study was reported by Cheng and coworkers 36,37 in which they studied PS brushes formed by the block-selective crystallization of PEO-b-PS and poly(L-lactic acid)-b-PS copolymers.…”
Section: The Definition Of a Polymer Brush By Characteristic Parametementioning
confidence: 99%
“…The new signal demonstrates the line broadening expected when the 1,1,1-trifluorobutane fragment is bound to the rigid network backbone of 1. The absence of other signals in the 19 F NMR spectrum indicated that no significant side reactions involving TFIB took place. Therefore, it was concluded that there were little to no 1,1,1-trifluorobutane radical fragments formed in solution, indicating that the primary reactive sites in the reaction solution were at the surface of 1.…”
Section: Resultsmentioning
confidence: 99%
“…18 Physisorption is characterized by adsorption of one polymer chain onto another, [19][20][21] whereas both grafting methods involve a chemical reaction between the substrate surface and the polymer chain forming a covalent bond attachment (chemisorption). 18 Although each method produces interesting physical characteristics at the substrate surface, the 'grafting from' method is of particular interest.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation